Putative MicroRNA-mRNA Networks Upon Mdfi Overexpression in C2C12 Cell Differentiation and Muscle Fiber Type Transformation - Huang, Bo; Jiao, Yiren; Zhu, Yifan; Ning, Zuocheng; Ye, Zijian; Li, Qing X.; Hu, Chingyuan; Wang, Chong (Frontiers in Molecular Biosciences, 2021)
Mdfi, an inhibitor of myogenic regulatory factors, is involved in myoblast myogenic development and muscle fiber type transformation. However, the regulatory network of Mdfi regulating myoblasts has not been revealed. In this study, we performed microRNAs (miRNAs)-seq on Mdfi overexpression (Mdfi-OE) and wild-type (WT) C2C12 cells to establish the regulatory networks. Comparative analyses of Mdfi-OE vs. WT identified 66 differentially expressed miRNAs (DEMs). Enrichment analysis of the target genes suggested that DEMs’ function DEMs may be involved in myoblast differentiation and muscle fiber type transformation through MAPK, Wnt, PI3K-Akt, mTOR, and calcium signaling pathways. miRNA-mRNA interaction networks were suggested along with ten hub miRNAs and five hub genes. We also putatively identified eight hub miRNAs and eleven hub genes in the networks of muscle fiber type transformation. Hub miRNAs mainly play key regulatory roles in muscle fiber type transformation through the PI3K-Akt, MAPK, cAMP, and calcium signaling pathways. Particularly, the three hub miRNAs (miR-335-3p, miR-494-3p, and miR-709) may be involved in both myogenic differentiation and muscle fiber type transformation. These hub miRNAs and genes might serve as candidate biomarkers for the treatment of muscle- and metabolic-related diseases.